2011
DOI: 10.2340/16501977-0797
|View full text |Cite
|
Sign up to set email alerts
|

Unified Balance Scale: An activity-based, bed to community, and aetiology-independent measure of balance calibrated with Rasch analysis

Abstract: The new scale (Unified Balance Scale) holds proven measurement properties and may be a candidate tool for "bed to community" balance measurement for patients with balance problems within the neuro-rehabilitation setting. Future studies are warranted to explore further its external validity and other clinical properties, as well as to improve its usability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 14 publications
0
52
1
Order By: Relevance
“…Under the definition of the BBS, our sample is expected to represent a population of patients presenting low risk of falling (BBS > 45). BBS, on the other hand, is known to present a ceiling effect [13, 43], that could possibly explain the differences observed in instrumented analysis between the HS and our sample of high-BBS patients. In our analysis we observed significant differences between the balance features calculated from the HS and the MS for all the traditional features (with the exclusion of ML path length and average speed in the eyes-open condition).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the definition of the BBS, our sample is expected to represent a population of patients presenting low risk of falling (BBS > 45). BBS, on the other hand, is known to present a ceiling effect [13, 43], that could possibly explain the differences observed in instrumented analysis between the HS and our sample of high-BBS patients. In our analysis we observed significant differences between the balance features calculated from the HS and the MS for all the traditional features (with the exclusion of ML path length and average speed in the eyes-open condition).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria for the study were the presence of neurological conditions in addition to MS, impaired cognitive functions and presence of mild dementia referred as a Mini Mental Status Examination score less than 24. Before the beginning of the instrumented balance tests, the following tests were administered to MS subjects: Time Up and Go test (TUG), Berg Balance Scale test (BBS; BBS < 45 indicates fall risk [42]) and the Unified Balance Scale test (UBS) [43]. Eighteen age-matched healthy control subjects (HS group, 6 males, 12 females; age = 52.8 ± 12.8 years; height = 167.1 ± 8.3 cm; body mass 65.4 ± 13.2 kg) were also recruited and tested in this study.…”
Section: Methodsmentioning
confidence: 99%
“…We selected balance measures that explored a broad range of motor tasks (both static and dynamic), were suitable for assessing ambulatory patients and were less susceptible to a ceiling effect [2830]. We assessed balance and mobility using the CB&M. This 13-item scale measures challenging motor tasks necessary for mobility in the community.…”
Section: Methodsmentioning
confidence: 99%
“…Marais and Andrich (2008b) investigated dependence at a critical residual correlation value of 0.1, but a value of 0.3 has also often been used (see e.g. La Porta et al, 2011;Das Nair et al, 2011;Ramp et al 2009;Røe, et al 2014), and critical values of 0.5 (ten Klooster et al 2008;Davidson et al 2004) and even 0.7 (González-de Paz et al, 2014) can be found in use.…”
Section: Critical Values Of Residual Correlationsmentioning
confidence: 99%